Patient-reported outcome for 17,648 patients in 5 different Swedish orthopaedic quality registers before and 1 year after surgery: an observational study - Maria C Cöster; Ann Bremander; Anna Nilsdotter (Acta Orthopaedica, 2023)
Background and purpose: The EQ-5D is a patientreported outcome measure (PROM). To make priorities and allocate resources between patients and surgical procedures it is necessary to evaluate outcome differences, which is why comparing PROMs between registers is important. We compared EQ-5D data and the follow-up rate for selected diagnoses reported to Swedish orthopedic registers before and 1 year after surgery. Patients and methods: Patients from 5 orthopedic registers (Swespine, Swedish Hip Arthroplasty Register, Swedish Knee Arthroplasty Register, Swedankle, and Swefoot) who, in 2014–2018, underwent surgery in southern Sweden were included in the study. Data on the EQ-5D index, individual questions, and the EQ-VAS at baseline and at the 1-year follow-up was compared. Results: 17,648 patients had completed the EQ-5D pre- and 1-year postoperatively. The follow-up rate ranged from 32% to 88%. All registers showed a statistical and clinically relevant improvement in the EQ-5D index (mean improvement 0.29–0.39), where patients who underwent hip arthroplasties experienced the largest improvement. The EQ-5D index improvements in patients with foot and ankle surgeries were larger than for patients with knee arthroplasties and spinal surgeries. The dimensions “self-care” and “usual activities” had the largest change in patients reporting “some problems.” Conclusion: All 5 registers showed a clinically relevant improvement 1 year postoperatively regarding the EQ-5D index, supporting continuous resource allocation to these groups of patients and surgical procedures. However, using PROM data to present register differences was challenged by the high number of non-responders.